A concrete anti-cracking waterproofing agent and a preparation method thereof
Patent Information
- Application Number
- CN202610959478.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-16
AI Technical Summary
[0004]但现有解决方案均未能从根本上解决钙矾石晶体孔道脱水收缩的本质缺陷,存在各自无法突破的技术瓶颈
[0031]1. This invention addresses the defect of late-stage shrinkage rebound in ettringite-type expansive agents at the crystal structure level. Through a pre-synthesis process, borate ions are embedded within the one-dimensional channels of ettringite. Utilizing the resulting multiple hydrogen bond network and rigid spatial constraints, these ions act like molecular pillars, preventing dehydration and shrinkage within the channels. While retaining the high early-stage expansion efficiency of ettringite, this invention significantly improves the long-term volume stability of concrete, avoids secondary cracking in later stages, and substantially extends the service life of engineering structures.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of concrete admixtures, and more particularly to a concrete crack-resistant and waterproofing agent and its preparation method. Background Technology
[0002] Concrete, as the most widely used building material globally, suffers from shrinkage cracking, which is the primary cause of structural leakage, steel corrosion, and durability deterioration. Economic losses due to concrete cracking reach hundreds of billions of yuan annually. Among numerous concrete shrinkage compensation technologies, ettringite-based expansive agents, with their advantages of high expansion efficiency, low cost, and ease of use, occupy more than 80% of the domestic concrete expansive agent market share and are widely used in basements, subways, tunnels, water conservancy projects, and other fields with high requirements for waterproofing and crack resistance. The core working principle of ettringite-based expansive agents is to generate needle-like ettringite crystals through hydration, causing volume expansion that counteracts the chemical shrinkage, drying shrinkage, and temperature shrinkage of concrete, thereby achieving the purpose of crack resistance and waterproofing. However, ettringite crystals themselves have inherent structural defects that are difficult to overcome; they consist of positively charged [Ca3Al(OH)6·12H2O]... 3+ The columnar units are arranged parallel to the c-axis to form a three-dimensional framework, with continuous channels of approximately 1 nm in diameter between the framework. These channels are filled with mobile sulfate ions and water of crystallization molecules. Under dry conditions, the zeolite water and some of the water of crystallization within the channels undergo reversible loss, leading to radial shrinkage of the channels and a 15%-20% reduction in crystal volume. This causes the concrete to expand initially and then shrink, and in severe cases, it can even trigger secondary cracking, completely eliminating its crack resistance and waterproofing effect. This problem has become the core bottleneck restricting the long-term performance improvement of ettringite-based expansive agents.
[0003] To address the issue of instability in the later stages of ettringite-based expansive agents, scholars and engineers both domestically and internationally have conducted extensive research and proposed various improvement schemes. The most mainstream approach is the dual-expansion-source compounding technology, which combines the ettringite-based expansive agent with other expansion sources such as lightly calcined magnesia and calcium oxide, utilizing the differences in hydration expansion rates between different sources to achieve complementary early and later expansion. Secondly, there is surface coating modification technology, which uses materials such as resin and paraffin to coat the surface of ettringite clinker particles, slowing down the hydration rate and reducing moisture loss. Additionally, there is organic modification technology, which incorporates water-reducing agents, retarders, and other organic components into the expansive agent to optimize concrete workability. Finally, there is fiber reinforcement technology, which combines steel fibers and polypropylene fibers with the expansive agent, using the bridging effect of the fibers to inhibit crack propagation. These technologies have improved the performance of ettringite-based expansive agents to some extent and partially solved the problem of short-term cracking in engineering applications.
[0004] However, existing solutions fail to fundamentally address the inherent defect of ettringite crystal pore dehydration and shrinkage, each facing its own insurmountable technical bottlenecks. In the dual-expansion-source compounding technology, the expansion rate of magnesium oxide is greatly affected by calcination temperature and fineness, resulting in poor batch stability and insufficient early expansion, failing to effectively compensate for early concrete shrinkage. Surface coating modification technology's coating layer is easily damaged by mechanical forces during concrete mixing, losing its slow-release effect. Simultaneously, the coating layer hinders the normal hydration of ettringite, leading to decreased expansion efficiency. In organic modification technology, the organic components easily compete with polycarboxylate superplasticizers for adsorption, causing severe slump loss and deteriorated workability. Fiber reinforcement technology not only significantly increases engineering costs but also suffers from uneven fiber dispersion and affects concrete pumpability. More importantly, all the above modification methods remain at the crystal surface or intergranular scale, never penetrating the internal pore structure of ettringite crystals, thus failing to fundamentally prevent pore dehydration and shrinkage, making it difficult to completely solve the industry problem of late-stage shrinkage cracking in concrete. Summary of the Invention
[0005] This invention addresses the shortcomings of existing technologies by providing a concrete crack-resistant and waterproofing agent and its preparation method.
[0006] To achieve the above objectives, the present invention adopts the following technical solution: a concrete crack-resistant and waterproofing agent, comprising the following components by weight: pre-synthetic boron-substituted ettringite powder: 80-90 parts, active activator: 3-10 parts, active mineral admixture: 5-15 parts, and retarding regulator: 0.3-3 parts.
[0007] Preferably, the chemical formula of the pre-synthesized boron-substituted ettringite powder is:
[0008] 3CaO·Al2O3·3(CaSO4) 1-x (Ca[B(OH)4]2) x ·32H2O;
[0009] Where x is the degree of boron substitution, and its value ranges from 0.03 to 0.12.
[0010] Preferably, the active activator is a compound of anhydrous sodium sulfate and aluminum sulfate octadecahydrate in a mass ratio of 2.5-3.5:1, and the fineness requirement is to pass through a 0.08mm square hole sieve with a sieve residue of ≤5%.
[0011] Preferably, the active mineral admixture is selected from at least one of metakaolin, ultrafine slag powder, and silica fume, with a specific surface area ≥ 600 m². 2 / kg.
[0012] Preferably, the retarding regulator is sodium gluconate or sodium citrate.
[0013] Furthermore, the present invention also provides a method for preparing a concrete crack-resistant and waterproofing agent, comprising the following steps:
[0014] (1) Dissolve calcium nitrate tetrahydrate, aluminum nitrate nonahydrate and anhydrous sodium sulfate in deionized water to prepare a mixed solution. Adjust the pH of the mixed solution to 12.5-13.5 with sodium hydroxide solution. Add sodium metaborate tetrahydrate, heat to 35-45℃, stir and react for 24-48 hours. After the reaction is completed, filter and wash with deionized water until no white precipitate is produced when the filtrate is tested with 5% barium chloride solution. After drying, the crude boron-substituted calcite is obtained.
[0015] (2) The crude boron-substituted ettringite was dispersed in an ethanol / water mixed solution to prepare a suspension. The temperature was raised to 55-65℃ with stirring, a surface modifier was added, and the reaction was stirred for 6-10 hours. After the reaction was completed, the filter cake was filtered, washed three times with anhydrous ethanol, dried, and then ground to obtain pre-synthesized boron-substituted ettringite powder.
[0016] (3) Add the pre-synthesized boron-substituted ettringite powder, active activator, active mineral admixture and retarder into a double spiral conical mixer, stir and mix at a speed of 50-70 r / min for 10-20 min, pass through a 0.08 mm square hole sieve, return the residue to the grinding, until all materials can pass through a 0.08 mm square hole sieve, to obtain a concrete crack-resistant and waterproof agent.
[0017] Preferably, in (1), the molar ratio of calcium nitrate tetrahydrate, aluminum nitrate nonahydrate, anhydrous sodium sulfate and sodium metaborate tetrahydrate is 3:1:1.5(1-x):3x; where x is the degree of boron substitution, x=0.03-0.12.
[0018] Preferably, the total ion concentration in the mixed solution in (1) is 0.35-0.45 mol / L.
[0019] Preferably, the concentration of the sodium hydroxide solution in (1) is 1-5 mol / L.
[0020] Preferably, the volume ratio of ethanol to water in the ethanol / water mixed solution in (2) is 9:1.
[0021] Preferably, the solid content of the suspension in (2) is 20-30%.
[0022] Preferably, the surface modifier in (2) is selected from at least one of methyltriethoxysilane, ethyltriethoxysilane, and propyltriethoxysilane, and the amount added accounts for 5-10% of the crude boron-substituted ettringite.
[0023] Preferably, the specific surface area of the pre-synthesized boron-substituted ettringite powder after grinding in (2) is 380-420 m². 2 / kg.
[0024] Preferably, the mechanism of action of the concrete crack-resistant and waterproofing agent of the present invention is explained as follows:
[0025] This invention addresses the inherent defect of ettringite-type expansion agents, which leads to volume instability in the later stages due to the dehydration and shrinkage of one-dimensional channels. It constructs a three-tiered crack-resistant and waterproof system comprising in-situ modification of crystal channels, synergistic protection with surface hydrophobicity, and complementary functions of multiple components. Its core logic begins with the identification of defects in the crystal structure of ordinary ettringite: the chemical composition of ordinary ettringite is 3CaO·Al₂O₃·3CaSO₄·32H₂O, and its crystal structure consists of positively charged [Ca₃Al(OH)₆·12H₂O]. 3+ The columnar units are arranged parallel to the c-axis to form a three-dimensional framework, with continuous channels of about 1 nm in diameter between the framework, and the channels are filled with movable SO4. 2- In a dry environment, ions and water of crystallization molecules cause the reversible loss of zeolite water and some water of crystallization within the pores, leading to radial shrinkage of the pores and a 15%-20% reduction in crystal volume, which in turn causes the concrete to expand initially and then shrink. To address this problem, this invention utilizes a pre-synthesis process to synthesize tetrahedral B(OH)4... - Ions are embedded in the pores of ettringite to form a stable boron-substituted ettringite solid solution, the general chemical formula of which is:
[0026] 3CaO·Al2O3·3(CaSO4) 1-x (Ca[B(OH)4]2) x ·32H2O; where x is the degree of boron substitution, 0.03-0.12; B(OH)4 - With SO4 2- Although both have a tetrahedral structure, their behavior within the ettringite channels is quite different, SO4 2- SO4 is connected to the pore walls by weak hydrogen bonds, which break during dehydration. 2- It can slide along with water molecules, causing the pores to contract, while B(OH)4 - After entering the pore, its four hydroxyl oxygen atoms react with the Ca atoms on the pore wall. 2+ And structural water molecules form a multi-hydrogen bond network, while B(OH)4 - Center B 3+ It has a strong affinity for oxygen, which locks the entire tetrahedron within the pores. Even if the surrounding water of crystallization is lost, these B(OH)4 atoms anchored to the pore walls remain intact. - They still occupy the original space, like rigid molecular pillars preventing the channels from shrinking radially.
[0027] This invention chooses to pre-synthesize boron-substituted ettringite in a pure aqueous solution system, rather than directly incorporating borate into concrete. The core consideration of this approach is that borate ions are recognized as retarder agents in cement systems, preferentially adsorbing onto the surface of cement particles or reacting with Ca... 2+ The formation of calcium borate precipitates inhibits the nucleation and growth of ettringite. If borate is added directly to concrete, it not only fails to replace the pores but also destroys the basic function of the expansive agent. However, in the pre-synthesis stage, borate ions are firmly embedded within the ettringite crystal lattice. When this powder is added to concrete as an expansive agent, boron exists in a fixed state and will not enter the liquid phase to interfere with cement hydration.
[0028] Although boron substitution stabilizes the pore structure from within the crystal, the surface of ettringite particles can still act as a gateway for moisture to enter and exit the crystal. This invention employs surface modifiers such as methyltriethoxysilane to hydrophobically modify boron-substituted ettringite powder. The silanol groups generated from silane hydrolysis are highly reactive. On one hand, they undergo dehydration condensation with the calcium hydroxyl groups on the ettringite crystal surface, forming chemical bonds; on the other hand, self-condensation reactions occur between the silanol groups, forming a three-dimensional network of hydrophobic films. These two condensation reactions work synergistically to form a uniform and robust hydrophobic protective layer on the ettringite surface. The outward-facing arrangement of methyl groups imparts surface hydrophobicity, preventing external moisture from entering the pores and causing excessive hydration, while also preventing the loss of internal crystal water and resulting volume shrinkage. This layer interacts with the B(OH)4 atoms within the pores. - The column supports form a waterproof structure with internal and external double locking.
[0029] In addition, an activator composed of anhydrous sodium sulfate and aluminum sulfate octadechydrate is added to the formula. The role of the activator is to release additional SO4 during the concrete hydration process. 2- And Al 3+ This process promotes the continued growth of pre-synthetic ettringite crystals, ensuring early expansion efficiency. The active mineral admixtures, through optimized particle size distribution, fill the gaps between powder particles and react with Ca(OH)2 generated during cement hydration to form CSH gel, further improving concrete density. Sodium gluconate or sodium citrate acts as a retarder to balance the potential early hydration acceleration effect of the active activator, ensuring concrete workability.
[0030] Compared with the prior art, the beneficial effects of the present invention are:
[0031] 1. This invention addresses the defect of late-stage shrinkage rebound in ettringite-type expansive agents at the crystal structure level. Through a pre-synthesis process, borate ions are embedded within the one-dimensional channels of ettringite. Utilizing the resulting multiple hydrogen bond network and rigid spatial constraints, these ions act like molecular pillars, preventing dehydration and shrinkage within the channels. While retaining the high early-stage expansion efficiency of ettringite, this invention significantly improves the long-term volume stability of concrete, avoids secondary cracking in later stages, and substantially extends the service life of engineering structures.
[0032] 2. This invention avoids the retarding side effects of free borate and the compatibility issues with polycarboxylate superplasticizers. The pre-synthesis process completely locks boron elements within the ettringite crystal lattice, preventing them from entering the cement paste liquid phase and interfering with the hydration process, and also preventing competitive adsorption with the superplasticizer. The product after addition has a setting time essentially the same as ordinary concrete, minimal slump loss, and excellent workability, meeting the engineering application requirements under different temperatures and construction processes.
[0033] 3. This invention constructs a synergistic waterproof and seepage-resistant system with internal and external double-locking. The internal borate ion stabilizes the pore structure, preventing interconnected microcracks caused by shrinkage. The external silane hydrophobic film blocks capillary seepage channels. Combined with the pozzolanic reaction of active mineral admixtures to fill pores, this significantly improves the density and seepage resistance of concrete. Simultaneously, it optimizes the interface transition zone between cement paste and aggregate, resulting in a synchronous improvement in the mechanical properties of concrete.
[0034] 4. The preparation process of this invention is simple and controllable, employing a room-temperature and atmospheric-pressure liquid-phase synthesis route. It eliminates the need for high-temperature calcination, resulting in low energy consumption, simple equipment requirements, and readily available and cost-controllable raw materials commonly used in industry, making it suitable for large-scale industrial production. Boron exists stably in the crystal structure in a chemically bonded form, with a leaching concentration far below the national standard limit, posing no environmental safety risks. Its overall cost-effectiveness is significantly superior to existing similar products. Detailed Implementation
[0035] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0036] Example 1: A specific preparation method for a concrete crack-resistant and waterproofing agent, comprising the following steps:
[0037] (1) Dissolve 3 mol calcium nitrate tetrahydrate, 1 mol aluminum nitrate nonahydrate and 1.455 mol anhydrous sodium sulfate in deionized water to prepare a mixed solution with a total ion concentration of 0.35 mol / L. Adjust the pH of the mixed solution to 12.5 with a sodium hydroxide solution with a concentration of 1 mol / L. Add 0.09 mol sodium metaborate tetrahydrate, heat to 35℃, stir and react for 24 h. After the reaction is completed, filter and wash with deionized water until no white precipitate is produced when the filtrate is tested with 5% barium chloride solution. After drying, the crude boron-substituted calcite is obtained.
[0038] (2) A suspension with a solid content of 20% was prepared by dispersing the boron-substituted ettringite crude product in an ethanol / water mixed solution (ethanol and water volume ratio of 9:1). The solution was heated to 55°C with stirring, and methyltriethoxysilane was added at an amount of 5% of the weight of the boron-substituted ettringite crude product. The mixture was stirred and reacted for 6 hours. After the reaction was completed, the mixture was filtered, and the filter cake was washed three times with anhydrous ethanol. After drying, the cake was ground to a specific surface area of 380 m². 2 / kg, to obtain pre-synthesized boron-substituted ettringite powder, whose chemical structural formula is: 3CaO·Al2O3·3(CaSO4). 0.97 (Ca[B(OH)4]2) 0.03 ·32H2O;
[0039] (3) Mix 80g of pre-synthesized boron-substituted ettringite powder with 3g of active activator (anhydrous sodium sulfate and aluminum sulfate octadecylhydrate compounded at a mass ratio of 2.5:1, with a fineness requirement of passing through a 0.08mm square hole sieve and a sieve residue of ≤5%) and 5g of metakaolin (specific surface area ≥600m²). 2 Add 0.3g sodium gluconate ( / kg) and 0.3g sodium gluconate to a double helical conical mixer and stir at 50r / min for 10min. Pass the mixture through a 0.08mm square hole sieve. Return the residue to the grinding mill until all materials can pass through the 0.08mm square hole sieve to obtain a concrete crack-resistant and waterproofing agent.
[0040] Example 2: A specific preparation method for a concrete crack-resistant and waterproofing agent, comprising the following steps:
[0041] (1) Dissolve 3 mol of calcium nitrate tetrahydrate, 1 mol of aluminum nitrate nonahydrate and 1.38 mol of anhydrous sodium sulfate in deionized water to prepare a mixed solution with a total ion concentration of 0.40 mol / L. Adjust the pH of the mixed solution to 13.0 with a 3 mol / L sodium hydroxide solution. Add 0.24 mol of sodium metaborate tetrahydrate, heat to 40℃, stir for 36 h. After the reaction is completed, filter and wash with deionized water until no white precipitate is produced when the filtrate is tested with 5% barium chloride solution. After drying, the crude boron-substituted calcite is obtained.
[0042] (2) Prepare a suspension with a solid content of 25% by dispersing the boron-substituted ettringite crude product in an ethanol / water mixed solution (ethanol and water volume ratio of 9:1). Heat the solution to 60°C with stirring, add ethyltriethoxysilane at an amount of 8% of the weight of the boron-substituted ettringite crude product, and stir the reaction for 6-10 hours. After the reaction is completed, filter the solution, wash the filter cake three times with anhydrous ethanol, dry it, and grind it to a specific surface area of 400 m². 2 / kg, to obtain pre-synthesized boron-substituted ettringite powder, whose chemical structural formula is: 3CaO·Al2O3·3(CaSO4). 0.92 (Ca[B(OH)4]2) 0.08 ·32H2O;
[0043] (3) Mix 85g of pre-synthesized boron-substituted ettringite powder with 5g of active activator (anhydrous sodium sulfate and aluminum sulfate octadecylhydrate compounded in a mass ratio of 3:1, with a fineness requirement of passing through a 0.08mm square hole sieve and a sieve residue of ≤5%) and 10g of ultrafine slag powder (specific surface area ≥600m²). 2 Add 1.5g of sodium gluconate ( / kg) to a double-helix conical mixer and stir at 60r / min for 15min. Pass the mixture through a 0.08mm square hole sieve. Return the residue to the grinding mill until all materials can pass through the 0.08mm square hole sieve to obtain a concrete crack-resistant and waterproofing agent.
[0044] Example 3: A specific preparation method for a concrete crack-resistant and waterproofing agent, comprising the following steps:
[0045] (1) Dissolve 3 mol of calcium nitrate tetrahydrate, 1 mol of aluminum nitrate nonahydrate and 1.305 mol of anhydrous sodium sulfate in deionized water to prepare a mixed solution with a total ion concentration of 0.45 mol / L. Adjust the pH of the mixed solution to 13.5 with a 5 mol / L sodium hydroxide solution. Add 0.36 mol of sodium metaborate tetrahydrate, heat to 45℃, stir for 48 h. After the reaction is completed, filter and wash with deionized water until no white precipitate is produced when the filtrate is tested with 5% barium chloride solution. After drying, the crude boron-substituted calcite is obtained.
[0046] (2) The boron-substituted ettringite crude product was dispersed in an ethanol / water mixed solution (ethanol and water volume ratio of 9:1) to prepare a suspension with a solid content of 30%. The temperature was raised to 65°C with stirring, and propyltriethoxysilane was added at an amount of 10% of the weight of the boron-substituted ettringite crude product. The mixture was stirred and reacted for 10 h. After the reaction was completed, the mixture was filtered, and the filter cake was washed three times with anhydrous ethanol. After drying, the cake was ground to a specific surface area of 420 m². 2 / kg, to obtain pre-synthesized boron-substituted ettringite powder, whose chemical structural formula is: 3CaO·Al2O3·3(CaSO4). 0.88 (Ca[B(OH)4]2) 0.12·32H2O;
[0047] (3) Add 90g of pre-synthesized boron-substituted ettringite powder, 10g of active activator (anhydrous sodium sulfate and aluminum sulfate octadecylhydrate are compounded at a mass ratio of 3.5:1, and the fineness requirement is to pass through a 0.08mm square hole sieve with a sieve residue of ≤5%), 15g of silica fume (specific surface area ≥600m2 / kg) and 3g of sodium citrate into a double spiral conical mixer, stir and mix at a speed of 70r / min for 20min, pass through a 0.08mm square hole sieve, and return the sieve residue to the grinding process until all materials can pass through a 0.08mm square hole sieve to obtain a concrete crack-resistant and waterproof agent.
[0048] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that steps (1) and (2) are omitted, and the pre-synthesized boron-substituted ettringite powder in (3) is replaced with ordinary ettringite powder with the same specific surface area.
[0049] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that steps (1) and (2) are omitted, the pre-synthesized boron-substituted ettringite powder in (3) is replaced with ordinary ettringite powder with the same specific surface area, and the molar amount of calcium ions in the added ordinary ettringite powder is calculated. Sodium metaborate is added after conversion according to calcium ion: boron ion = 1: 0.08.
[0050] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that, following the preparation method of Example 2, a chemical structure with the formula 3CaO·Al2O3·3(CaSO4) was prepared. 0.8 (Ca[B(OH)4]2) 0.2 Pre-synthesized boron-substituted ettringite powder with ·32H2O.
[0051] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (2) is omitted, and the boron-substituted ettringite crude product obtained in (1) is ground to a specific surface area of 400 μm. 2 / kg, to obtain pre-synthesized boron-substituted ettringite powder.
[0052] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that sodium metaborate tetrahydrate is replaced with sodium tetraborate.
[0053] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that sodium metaborate tetrahydrate is replaced with boric acid.
[0054] Performance testing:
[0055] All tests used a uniform dosage of crack-resistant and waterproofing agent: the total amount of cementitious material was 8%, and the cementitious material composition was P·O42.5 ordinary Portland cement, without the addition of other admixtures.
[0056] 1. Tests on restricted expansion rate and long-term volume stability: The tests were conducted according to GB 23439-2017 "Concrete Expansion Agent" standard. A 100mm×100mm×300mm restricted expansion rate mold was used, with an internal longitudinal steel reinforcement limiter. The concrete mix proportion was the same as in the example. The dosage of crack-resistant and waterproof agent was 8% of the total cementitious material. After the test blocks were formed, they were cured in the mold for 24 hours before demolding. After measuring the initial length, one group was placed in water at 20±2℃ for curing, and the restricted expansion rate in water was tested at 7 days and 28 days. The other group was cured in water for 7 days and then moved to air at 20±2℃ and 60±5% relative humidity for curing, and the restricted shrinkage rate in air was tested at 28 days, 90 days, and 180 days.
[0057] 2. Concrete workability and compatibility test with water-reducing agent: The test was conducted in accordance with GB / T 50080-2016 "Standard for Test Methods of Performance of Ordinary Concrete Mixtures". The standard slump cone method was used. The concrete mix proportion was fixed and the dosage of polycarboxylate water-reducing agent was uniformly 1.0% of the total cementitious materials. The initial slump and the slump after standing for 1 hour were tested for concrete with different anti-cracking and waterproofing agents. The slump loss rate was calculated. The ambient temperature was maintained at 20±2℃ during the test.
[0058] 3. Concrete permeability test: The test was conducted according to the water seepage height method in GB / T 50082-2024 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete". A frustum-shaped mold with an upper diameter of 175 mm, a lower diameter of 185 mm, and a height of 150 mm was used. After the test block was formed, it was cured under standard conditions for 28 days. The sides of the test block were sealed and then placed in a permeability tester. A water pressure of 0.8 MPa was applied and kept constant for 24 hours. After the test, the test block was split open to measure the water seepage height, calculate the relative permeability coefficient, and determine the permeability grade.
[0059] 4. Cement paste setting time test: The test was conducted according to GB / T 1346-2024 "Test Methods for Standard Consistency Water Requirement, Setting Time and Soundness of Cement". A Vicat apparatus was used for the standard method. First, the standard consistency water requirement was determined, and then the initial setting time and final setting time were tested in the standard consistency cement paste. The test environment temperature was 20±2℃ and the relative humidity was ≥90%.
[0060] 5. Concrete compressive strength test: The test was conducted in accordance with GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". A 100mm×100mm×100mm cube mold was used. After the test blocks were formed, they were cured under standard conditions for 3 days, 7 days and 28 days. The compressive strength was tested at each time. The strength value was multiplied by the size conversion factor of 0.95.
[0061] 6. Boron ion leaching toxicity test: The test was conducted according to the horizontal oscillation method in GB 5085.3-2007 "Identification Standard for Hazardous Waste - Leaching Toxicity Identification". 28-day-old concrete test blocks were crushed and passed through a 3mm sieve. 100g of the sample was weighed and placed in a 2L polyethylene bottle. 1L of deionized water was added as the leaching agent. After sealing, the sample was horizontally oscillated at a frequency of 110 times / min for 8 hours at 23±2℃. After standing for 16 hours, the leachate was filtered and collected. The boron concentration in the leachate was determined using an inductively coupled plasma optical emission spectrometer (ICP-OES).
[0062] The experimental results are shown in Table 1.
[0063] Table 1 Performance Test Results
[0064] Data Analysis:
[0065] As can be seen from the performance test data in Table 1, the concrete crack-resistant and waterproofing agent prepared in the embodiments of the present invention is significantly superior to the comparative examples in terms of long-term volume stability, compatibility with polycarboxylate superplasticizer, impermeability, and mechanical properties. It solves the industry pain point of traditional ettringite-type expansive agents that expand first and then shrink, while avoiding the retarding side effect of borate. Among them, Example 2 achieves the best balance between expansion performance, volume stability, workability, and cost, exhibiting the most outstanding overall performance.
[0066] Regarding the limitation of expansion rate and long-term volume stability, the early water expansion rate of Example 2 is comparable to that of ordinary ettringite expanding agent, which can meet the needs of early shrinkage compensation in concrete, while the later air shrinkage rate is much lower than that of all comparative examples. This is because Example 2 embeds an appropriate amount of borate ions into the pores of ettringite through a pre-synthesis process. The multiple hydrogen bond network and rigid spatial constraints formed by borate ions and pore walls act like molecular pillars, preventing radial shrinkage of the pores under dry conditions. Comparative Example 1 used ordinary ettringite, where sulfate ions in the pores easily slipped during dehydration, leading to severe shrinkage in the later stages. Comparative Example 2 directly dry-mixed sodium metaborate with ordinary ettringite, where free borate inhibited the nucleation and growth of ettringite, resulting in insufficient early expansion and no significant improvement in later shrinkage. Comparative Example 3 had excessively high boron substitution, which damaged the integrity of the ettringite crystal structure, leading to a significant decrease in early expansion efficiency and failing to meet engineering requirements. Comparative Example 4 did not undergo surface hydrophobic modification, allowing water to easily enter and exit the pores, exacerbating volume changes. Comparative Examples 5 and 6 used borax and boric acid as boron sources, and the side reactions generated during the pre-synthesis process reduced the boron substitution efficiency, resulting in a higher later shrinkage rate than Example 2.
[0067] Regarding concrete workability and compatibility with the water-reducing agent, the 1-hour slump loss rate of Example 2 was significantly lower than that of the comparative examples, demonstrating excellent compatibility with the polycarboxylate water-reducing agent. This is attributed to the pre-synthesis process, which completely locks boron within the ettringite lattice, avoiding competitive adsorption between free borate and the water-reducing agent. Furthermore, the boron-substituted surface charge characteristics of ettringite are more stable, preventing the strong adsorption of negatively charged polycarboxylate molecules as seen in ordinary ettringite. In Comparative Example 1, the surface of ordinary ettringite is positively charged, leading to rapid slump loss due to the large adsorption of water-reducing agent molecules. In Comparative Example 2, free borate and the water-reducing agent co-adsorb on the cement particle surface, further exacerbating workability degradation. In Comparative Examples 5 and 6, residual byproducts from boron source hydrolysis slightly affect the dispersion of the water-reducing agent, resulting in higher slump loss rates than Example 2. Comparative Examples 3 and 4, without altering the surface adsorption characteristics of ettringite, exhibit compatibility similar to Example 2 but still slightly inferior.
[0068] In terms of impermeability, Example 2 showed a significantly higher impermeability grade than all comparative examples, with a relative permeability coefficient reduced by more than an order of magnitude. This is because Example 2 constructed a double-locked waterproof structure with internal pore column support and an external hydrophobic membrane: the internal borate stabilized the pore structure, preventing microcracks caused by shrinkage; the external silane hydrophobic membrane blocked capillary seepage channels, and the synergistic effect of the two significantly improved the density and waterproofing ability of the concrete. Comparative Example 1, with its ordinary ettringite, produced a large number of interconnected pores due to later shrinkage, resulting in the worst impermeability; Comparative Example 4 omitted the surface modification step, and the lack of a hydrophobic barrier made it easy for water to penetrate, significantly reducing its impermeability; Comparative Examples 2 and 6 had insufficient early hydration of concrete due to the retarding effect, resulting in high internal porosity and poor impermeability; although boron substitution played a certain role in pore stabilization in Comparative Examples 3 and 5, the surface modification effect or crystal integrity was not as good as Example 2, and their impermeability performance still lagged behind.
[0069] Regarding setting time, the initial and final setting times of Example 2 were basically the same as those of ordinary cement, with no obvious retardation. This is because the pre-synthesis process firmly embeds borate ions into the ettringite lattice, with almost no free boron entering the cement paste to interfere with the hydration process. In Comparative Example 2, free sodium metaborate was directly added, and the borate formed a dense coating film on the surface of cement particles, severely hindering clinker dissolution and hydration reactions, resulting in a significant extension of setting time, which could not meet normal construction requirements. In Comparative Examples 5 and 6, borax and boric acid were used as boron sources, and some boron did not completely enter the lattice during the pre-synthesis process, resulting in residual free boron that extended the setting time to varying degrees. The high boron substitution degree of Comparative Example 3 slightly affected the hydration activity of ettringite, and the setting time was slightly extended. The setting times of Comparative Examples 1 and 4 were close to those of ordinary cement, but other properties were far inferior to those of Example 2.
[0070] Regarding compressive strength, the compressive strength of Example 2 at all ages was higher than that of the comparative example, and the later strength growth was stable. This is partly because the active mineral admixture reacts with the calcium hydroxide produced by cement hydration in a pozzolanic reaction, generating more CSH gel, which fills the pores inside the concrete; on the other hand, the boron-substituted ettringite has a more complete crystal structure and a denser interfacial transition zone, improving the overall mechanical properties of the concrete. Comparative Example 2 suffered from severe retardation, resulting in a slow hydration process and a significant decrease in both early and later strength; the retardation effect of Comparative Examples 5 and 6 also had an adverse impact on strength development; Comparative Example 4 did not undergo surface modification, resulting in a weaker interfacial bond between ettringite and cement paste, leading to a slight decrease in strength; the high boron substitution degree of Comparative Example 3 disrupted the crystal structure of ettringite, resulting in lower strength than Example 2; the ordinary ettringite in Comparative Example 1 underwent microcracks due to later shrinkage, leading to lower strength than Example 2.
[0071] Regarding the leaching toxicity of boron ions, the boron leaching concentration in Example 2 was far below the national standard limit, demonstrating good environmental safety. This is because the pre-synthesis process allows boron to exist in a chemically bonded form within the ettringite lattice, resulting in a stable structure that is difficult to leach. In Comparative Example 2, the free sodium metaborate did not participate in the hydration reaction and was easily leached from the concrete, resulting in the highest boron concentration. In Comparative Examples 5 and 6, due to the side reaction of boron source hydrolysis, some boron existed in an adsorbed state on the crystal surface, leading to higher leaching concentrations than in Example 2. The boron fixation effects of Comparative Examples 3 and 4 were similar to those of Example 2, but their overall performance was not as good as that of Example 2.
[0072] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A concrete crack-resistant and waterproofing agent, characterized in that, It includes the following components by weight: pre-synthesized boron-substituted ettringite powder: 80-90 parts, active activator: 3-10 parts, active mineral admixture: 5-15 parts, and retarder: 0.3-3 parts; The general chemical formula of the pre-synthesized boron-substituted ettringite powder is: 3CaO·Al2O3·3(CaSO4) 1-x (Ca[B(OH)4]2) x ·32H2O; Where x represents the degree of boron substitution.
2. The concrete crack-resistant and waterproofing agent according to claim 1, characterized in that, The active activator is a compound of anhydrous sodium sulfate and aluminum sulfate octadecade hydrate in a mass ratio of 2.5-3.5:
1. The fineness requirement is to pass through a 0.08mm square hole sieve with a sieve residue of ≤5%.
3. The concrete crack-resistant and waterproofing agent according to claim 1, characterized in that, The active mineral admixture is selected from at least one of metakaolin, ultrafine slag powder, and silica fume, with a specific surface area ≥ 600 m². 2 / kg.
4. The concrete crack-resistant and waterproofing agent according to claim 1, characterized in that, The retarding regulator is sodium gluconate or sodium citrate.
5. The method for preparing the concrete crack-resistant and waterproofing agent according to any one of claims 1-4, characterized in that, Includes the following steps: (1) Dissolve calcium nitrate tetrahydrate, aluminum nitrate nonahydrate and anhydrous sodium sulfate in deionized water to prepare a mixed solution. Adjust the pH of the mixed solution to 12.5-13.5 with sodium hydroxide solution. Add sodium metaborate tetrahydrate, heat to 35-45℃, stir and react for 24-48 hours. After the reaction is completed, filter and wash with deionized water until no white precipitate is produced when the filtrate is tested with 5% barium chloride solution. After drying, the crude boron-substituted calcite is obtained. (2) The crude boron-substituted ettringite was dispersed in an ethanol / water mixed solution to prepare a suspension. The temperature was raised to 55-65℃ with stirring, a surface modifier was added, and the reaction was stirred for 6-10 hours. After the reaction was completed, the filter cake was filtered, washed three times with anhydrous ethanol, dried, and then ground to obtain pre-synthesized boron-substituted ettringite powder. (3) Add the pre-synthesized boron-substituted ettringite powder, active activator, active mineral admixture and retarder into a double spiral conical mixer, stir and mix at a speed of 50-70 r / min for 10-20 min, pass through a 0.08 mm square hole sieve, return the residue to the grinding, until all materials can pass through a 0.08 mm square hole sieve, to obtain a concrete crack-resistant and waterproof agent.
6. The method for preparing the concrete crack-resistant and waterproofing agent according to claim 5, characterized in that, In (1), the molar ratio of calcium nitrate tetrahydrate, aluminum nitrate nonahydrate, anhydrous sodium sulfate, and sodium metaborate tetrahydrate is 3:1:1.5(1-x):3x; where x is the degree of boron substitution, x=0.03-0.
12.
7. The method for preparing the concrete crack-resistant and waterproofing agent according to claim 5, characterized in that, The total ion concentration in the mixed solution in (1) is 0.35-0.45 mol / L; the concentration of the sodium hydroxide solution is 1-5 mol / L.
8. The method for preparing the concrete crack-resistant and waterproofing agent according to claim 5, characterized in that, In the ethanol / water mixed solution described in (2), the volume ratio of ethanol to water is 9:1; the solid content of the suspension is 20-30%.
9. The method for preparing the concrete crack-resistant and waterproofing agent according to claim 5, characterized in that, The surface modifier is selected from at least one of methyltriethoxysilane, ethyltriethoxysilane, and propyltriethoxysilane, and the amount added accounts for 5-10% of the crude boron-substituted ettringite.
10. The method for preparing the concrete crack-resistant and waterproofing agent according to claim 6, characterized in that, The specific surface area of the pre-synthesized boron-substituted ettringite powder after grinding in (2) is 380-420 m². 2 / kg.